A new species of cylindrical bark beetle (Zopheridae: Colydiinae) from Vanuatu establishes in Hawaii - Bernard, Jared; Gillett, Conrad P. D. T. (Zootaxa, 2020)
We describe Bulasconotus scaccarius sp. nov., a new species of cylindrical bark beetle (Zopheridae: Colydiinae: Synchitini), elevating the number of described species in its genus to two. Despite discovering this species in Hawaii, we suspect, based on collections and survey data, that it is endemic to the South Pacific archipelago of Vanuatu and has only recently arrived in Hawaii. Evidence of the diet of closely related genera indicates that the new species may be a predator of ambrosia beetles (Curculionidae: Scolytinae), conceivably posing a risk to those that are endemic to Hawaii.